Detection of hyperoxaemia in neonates: data from three new pulse oximeters. Issue 3 (1st November 2002) - Bohnhorst, B; Peter, C S; Poets, C F
Abstract : Aim: To determine the sensitivity and specificity of three newly developed pulse oximeters in the detection of hyperoxaemia, defined as an arterial partial pressure of oxygen (Pao 2 ) of > 80 mm Hg. Methods: Spo 2 readings from three oximeters (Agilent Viridia (AgV), Masimo SET (MaS), Nellcor Oxismart (NeO)) were documented in 56 infants (median gestational age at birth 35.5 weeks, range 24–41) whenever an arterial blood gas was taken for clinical purposes. Blood samples were analysed within one minute in a Radiometer ABL 505 blood gas analyser and OSM3 co-oximeter. Results: Between 280 and 291 blood gases were analysed for each instrument; 105–112 showed a Pao 2 > 80 mm Hg. At an upper alarm limit of 95%, the three instruments detected hyperoxaemia with 93–95% sensitivity. Specificity at this alarm level ranged from 26 to 45%. The mean (SD) difference between arterial oxygen saturation and Spo 2 (bias) was −0.25 (2.5)% for AgV, −0.06 (2.5)% for MaS, and −0.91 (2.6)% for NeO (p < 0.01, NeO v AgV and MaS). Conclusion: These instruments detected hyperoxaemia with sufficient sensitivity at an upper alarm limit of 95%, but showed differences in their specificity, which was probably related to differences in measurement bias.